Pembaharuan Islam Muhammad Ibn Abdul Wahhab di Mesir - Solekha, Amalia (STUDIA: JURNAL HASIL PENELITIAN MAHASISWA, 2019)
A change that occurs in the life of Muslims in the millennial period today is sometimes not in accordance with the efforts of renewal of the thoughts of the reformers among the previous Islamic community. In the 18 M, a renewal movement in Egypt was born which was spearheaded by one of the leaders of reformation namely Muhammad Ibn Abdul Wahhab from Saudi Arabia. The background of the renewal movement by Muhammad Ibn Abdul Wahhab was due to a setback in the Muslim Community. Writing is an exposition to find out how renewal is carried out by the figure of reformer Muhammad Ibn Abdul Wahhab.